2002
DOI: 10.1023/a:1022589015687
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The glycosylation alterations of mouse small intestinal mucins during a 12-day infectious cycle caused by the parasite Nippostrongylus brasiliensis have been studied. The guanidinium chloride insoluble mucins were isolated at day 0 to 12 from the small intestine of infected and non-infected C57BL/6 mice. The O-linked oligosaccharides were released by reductive beta-elimination from the mucins and separated into neutral, sialylated and sulfated fractions. All fractions were analyzed by monosaccharide compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Mucin O -glycosylation has also been previously shown to be a dynamic system and glycan patterns are commonly altered as secondary effects to infection and inflammation. The Fut2 enzyme is known to be upregulated in the mouse small intestine upon infection and in cystic fibrosis (Bry et al, 1996; Holmen et al, 2002; Thomsson et al, 2002). Patients with ulcerative colitis have been shown to have a transient altered glycosylation of MUC2 that was reversed to normal when the patient went into remission (Holmén Larsson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mucin O -glycosylation has also been previously shown to be a dynamic system and glycan patterns are commonly altered as secondary effects to infection and inflammation. The Fut2 enzyme is known to be upregulated in the mouse small intestine upon infection and in cystic fibrosis (Bry et al, 1996; Holmen et al, 2002; Thomsson et al, 2002). Patients with ulcerative colitis have been shown to have a transient altered glycosylation of MUC2 that was reversed to normal when the patient went into remission (Holmén Larsson et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of fucose in the tissue during infection are consistent with the observed increase in transcription levels of FUT2 and FUT4 , coding for enzymes transfering Fuc α-1,2 and Fuc α-1,3 respectively, on mucins. Similarly in the small intestine of rats infected with N. brasiliensis , an induced fucosylation, due to an upregulation of Fut2 gene expression, has been reported [38]. Disulphide isomerases are a family of enzymes that play an important role in the process of disulphide bond formation of gel forming mucins [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…spiralis , T. muris and H . polygyrus 76, 77, 78, 79. It has yet to be determined whether these changes occur as a result of the inflammatory environment or to resolve the infection; clearly more research is required to define the precise role of mucin glycans.…”
Section: Gi Nematode Infection and Alterations In Mucin Glycomementioning
confidence: 99%
“…It has yet to be determined whether these changes occur as a result of the inflammatory environment or to resolve the infection; clearly more research is required to define the precise role of mucin glycans. Most of our current understanding of the central role that mucin glycosylation plays during inflammatory threat has come from challenging rodents with infectious agents,71, 77, 78 and there are data to suggest that during GI nematode infections, there are multiple changes in the expression of glycosyltransferases, the enzymes responsible for the synthesis of the glycan chains 75. Yamauchi et al77 have demonstrated that by day 2‐3 of T. spiralis infection, there is an increase in α‐2‐3‐sialyltransferase IV.…”
Section: Gi Nematode Infection and Alterations In Mucin Glycomementioning
confidence: 99%